HeLa-Cell Adherence Patterns of Enteropathogenic Escherichia coli Strains Isolated from Faecal Samples - MY Alikhani; AR Mirsalehian; MM Aslani (Iranian Journal of Public Health, 2007)
Background: Escherichia coli strains that cause nonbloody diarrhea in infants are known to present four distinct patterns of adherence to epithelial cells, namely, Localized (LA), Localized Adherence Like (LAL), Diffuse (DA) and Aggregative (AA) adherence. Strains with LA and AA are well recognized as a cause of diarrhea, but the role of strains with DA is controversial and strains with LAL have been more frequently isolated in diarrheal than asymptomatic cases. Methods: To determine the distribution of the different types of enteropathogenic E. coli (EPEC) adherence patterns in diarrhea, we studied 191 EPEC strains isolated from infants less than 5 years of age with and without diarrhea in Iran. Results: Totally 131 (68.5%) strains adhered to HeLa cells and 60 (31.5%) isolates did not. The results revealed that Localized Adherence (LA) was manifested by 30 of 111 (86%) strains isolated from diarrheal cases of which the most belonged to serogroups O86 and O55. Localized Adherence like (LAL) was exhibited by 16 and Aggregative Adherence (AA) by 9 strains isolated from patients. However, Diffuse Adherence (DA) was exhibited by 8 strains equally distributed between both diarrheal and healthy persons. Undefined Pattern (UDP) was observed in 24 strains. Conclusion: Overall, the results showed that LA, LAL and AA adherence significantly associated with diarrhea (P< 0.05).